Promoting theory of mind and emotion understanding in preschool settings: an exploratory training study - Grazzani, Ilaria (Frontiers in Psychology, 2024)
Introduction This new exploratory study is part of a larger ongoing follow-up project. Its specific aim was to verify whether an innovative European Program, primarily designed to enhance children’s social and emotional learning, led to gains in theory of mind and emotion understanding when implemented in preschool settings. Methods Thirty-four children (mean age: 56.4 months; SD: 10.1; range: 40–70 months) participated in the study. They were randomly and equally divided into a training group and a control group. The training sample completed eight linguistic-conversational activities drawn from the Program, in groups of 5 to 6 children, over 8 weeks. The activities were based on listening to stories and/or watching videos and then thinking and talking about the inner world (thoughts and emotions) of the story characters as well as the participants’ own inner states. During the training phase, the children in the control group engaged in drawing or free play activities. At both the pre-test and post-test phases of the study, all the children completed a language test, a battery of theory of mind (ToM) tasks (including ‘change of location’ and ‘unexpected content’ tasks), and the Test of Emotion Comprehension which evaluates nine components of emotion understanding (EU). The validated national versions of the tests were administered in all cases. Results Significant differences were identified between the training and control groups. Indeed, the participants in the Program training activities, which were based on conversational exchanges between an adult and a group of children, as well as among the children themselves, outperformed the control participants on both overall theory of mind and overall emotion understanding. A more detailed analysis showed that the training group outperformed the control group in relation to both specific components of EU and the ‘change of location’ ToM task. Discussion The results of this exploratory study suggest that the Program is effective at enhancing preschoolers’ social understanding and thus merits implementation in preschool settings.